Role of interleukins in the detection of neonatal sepsis: a network meta-analysis - Xing, Wei; Wang, Ying; Liu, Jiao; Pei, Jie; Yu, Chengyong (Frontiers in Pediatrics, 2023)
The purpose of the network meta-analysis was to make a more comprehensive comparison of different interleukins in the detection of neonatal sepsis and to pose clues in the field of clinical practice.Methods Electronic databases of PubMed, Web of Science and Embase were systematically searched. Eligible studies included diagnostic tests utilizing interleukins to detect neonatal sepsis. We calculated pooled sensitivity, specificity, positive Likelihood Ratio (PLR) and negative Likelihood Ratio (NLR), diagnostic odds ratio (DOR), and superiority index.Fifteen studies including 1369 neonates diagnosed of sepsis were included in this meta-analysis. For the detection of early-onset sepsis in neonates, the pooled sensitivity was 0.91 (95% CI: 0.81, 0.97; I 2 = 0%, p = 0.946) and the pooled specificity was 0.98 (95% CI: 0.87, 0.97; I 2 = 46.3%, p = 0.172) for IL-8.For the detection of late-onset sepsis in neonates. the sensitivity was 0.96 (95% CI: 0.85, 1.00; I 2 = NA, p = NA) and the pooled specificity was 1.00 (95% CI: 0.92, 1.00; I 2 = NA, p = NA) for IL-27. Results of ANOVA model revealed that the superiority index of IL-6, IL-8, IL-10, and IL-27 were 1.20 (0.14, 5.00), 5.14 (0.33, 7.00), 0.75 (0.14, 5.00), and 1.31 (0.14, 5.00) in the detection of early-onset neonatal sepsis. Superiority index of 5.00), 1.04 (0.20, 5.00), and 2.21 (0.20, 5.00) in the detection of late-onset neonatal sepsis.Findings of this network meta-analysis suggest that interleukins including IL-6, IL-8, IL-10, and IL-27 may have favorable performance in the detection of 3 neonatal sepsis. IL-8 was more accurate in the detection of early-onset sepsis in neonates. IL-27 was more accurate in the detection of late-onset neonatal sepsis.